2017
DOI: 10.1002/cctc.201700792
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Nano‐Fe3O4 on α‐Al2O3 Catalysts for Fischer–Tropsch Synthesis to Lower Olefins: Promoter and Size Effects

Abstract: The Fischer–Tropsch synthesis to lower olefins (FTO) is a desirable nonpetroleum‐based route to produce basic chemicals. A novel two‐step method was applied to synthesize iron‐based supported catalysts, which is to prepare nano‐Fe3O4 first by thermal decomposition method and sequentially load them on α‐Al2O3 by impregnation. TEM and XRD results manifested that the controllable, uniform Fe3O4 nanoparticles are monodispersed on the surface of α‐Al2O3. H2‐TPR demonstrated that the reduction of Fe species was faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…As is well accepted, the FTO catalyst must be activated by reduction and carburization before the reactions, and the reduction and carburization of iron oxides have a signicant inuence on the performance of the catalyst. 57 The hydrogen temperatureprogrammed reduction (H 2 -TPR) can verify the reduction ability, and to conrm the interaction between iron and the support. Fig.…”
Section: Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…As is well accepted, the FTO catalyst must be activated by reduction and carburization before the reactions, and the reduction and carburization of iron oxides have a signicant inuence on the performance of the catalyst. 57 The hydrogen temperatureprogrammed reduction (H 2 -TPR) can verify the reduction ability, and to conrm the interaction between iron and the support. Fig.…”
Section: Supportmentioning
confidence: 99%
“…5 Besides, the acidity of the support exerts its inuence on its interaction with the active phase, and on the catalytic performance. [6][7][8][9] The Hägg iron carbide (c-Fe 5 C 2 ) has been generally accepted as the active phase for the FT reactions. [10][11][12] Many previous works found that the c-Fe 5 C 2 crystal facet greatly affects the catalytic performance and the formation of the Hägg iron carbide strongly depends on the interaction between the iron species and the support.…”
Section: Introductionmentioning
confidence: 99%
“…Olefin, especially lower olefin (C 2 ‐C 4 ), is a series of crucial basic building‐block chemicals for production of a wide range of plastics, solvents, drugs, and cosmetics. Lower olefins are generally produced by steam cracking of crude oil–derived naphtha, the methanol‐to‐olefins (MTO) process, or by the direct F‐T route (FTO) from a coal‐based feedstock syngas . A large amount of studies has been devoted to syngas conversion to lower olefins by F‐T synthesis over Fe catalysts as they are more selective towards olefins than Co or Ru F‐T catalysts.…”
Section: F‐t Synthesis For High‐value Chemicals Productionmentioning
confidence: 99%
“…The performance of iron catalysts can be greatly improved by adding “electronic” or chemical promoters to the catalyst formula . Among such promoters, potassium, sodium, copper, and manganese have been proposed. Recently, the TPR‐EXAFS technique confirmed that doping FTS catalysts with copper and alkali metals remarkably promotes the carburization rate relative to the undoped catalyst.…”
Section: Introductionmentioning
confidence: 99%